Tradisi Lebaran Kupatan di Desa Banjar Mulai Kecataman Bara Datu Kabupaten Lampung Waykanan dalam Persprktif Living Hadis - Suryani Suryani; Yezi Zurmavia (Universitas Islam Negeri Fatmawati Sukarno, 2022)
The method used in the research is a qualitative method with a phenomenological analysis approach which is used as a tool for the phenomenon or tradition of Eid Kupatan. This approach is also used to explore the meaning and values that exist in the kupatan tradition. As supporting tools in this research, the author also uses interview methods, documentation and participant observation as a concrete form of field research. The results of the research show that the traditional process of Eid Kupatan in the month of Shawwal begins with fasting in Shawwal, reading prayers together, visiting the residences of village elders and then continuing around to the residents' houses. The Eid Kupatan community is a form of bond that strengthens ties of friendship and a form of alms between the people of Banjar Mulia Village, as well as a form of solidarity to unite people so that harmony and tranquility can be realized in Banjar Mulia Village. As a basis for the Lebaran Kupatan tradition in Banjar Mulia Village, Lampung Way Kanan Regency, there are hadiths contained in the Kupatan tradition, hadiths about Shawwal fasting, hadiths about friendship, hadiths about almsgiving and hadiths about glorifying guests.